Management and outcome of patients with pancreatic trauma - Ravinder Pal Singh; Anuj Mahajan; Jaspal Singh Selhi; Nikhil Garg; Honey Chahal; Manjyot Bajwa (Nigerian Journal of Surgery, 2017)
Introduction: Pancreatic trauma is a rare entity occurring in 0.2% of patients with blunt trauma abdomen. Once the diagnosis is made, the management of patients is dependent on multiple variables. Conservative management, suture repair, drainage, and resection have been utilized with varying degree of success. This study is aimed to evaluate the management of patients with pancreatic trauma. Materials and Methods: This was a prospective study done in the Department of Surgery in Dayanand Medical College and Hospital where forty hemodynamically stable patients diagnosed to have pancreatic trauma on contrast-enhanced computed tomography abdomen were included in the study. Results: Out of forty patients taken in this study, 38 were male and two were female with age ranging from 3 to 50 years. Road traffic accident was the most common cause of pancreatic injury. Pancreatic injuries were graded according to the American Association for Surgery in Trauma scale. Twelve patients had Grade I and II injuries. Grade III was the most common injury occurring in 14 patients. Twenty-four patients underwent surgical management. Mortality rate was 45% and it was in direct correlation with the severity of injury. Conclusion: Grade I and II pancreatic injury can be managed conservatively depending upon the hemodynamic status of the patient. Grade III and IV injuries have a better prognosis if managed surgically.